Bookstore Operations Practices of a Private Higher Education Institution in the Philippines: Basis for the Proposed Guidelines for Effective Bookstore Management - Ohlie I Macatangay; Jesus Briones; Flormando P Baldovino; Lalaine V Manalo (Research Synergy Foundation, 2025)
Bookstore management plays a vital role in ensuring timely and cost-effective supply of educational materials. This study examined bookstore operations practices in a private higher education institution (HEI) in the Philippines. This descriptive-quantitative research used researcher-structured questionnaire distributed in-person to the 133 respondents composed of 66 college and 67 senior high school students of the subject HEI. The data gathered were analyzed with statistical tools such as frequency, percentage, standard deviation, weighted mean, and Spearman rank correlation. Results revealed that the bookstore operations was found well-managed considering its proper inventory management practices and the highly acceptable level of customer service provided to their customers. The efficient management of the bookstore justifies the acceptable customer satisfaction ratings and the non-existence of serious problems related to bookstore operations. The study also revealed a significant relationship between bookstore operations practices in terms of inventory management, and customer satisfaction in terms of value and pricing. However, there was no significant relationship revealed between inventory management and customer satisfaction in terms of inventory and availability. Likewise, no significant relationships were revealed between customer service, and both dimensions of customer satisfaction (inventory and availability, and value and pricing). Based on these findings, proposed guidelines were developed to further enhance bookstore management practices. This study serves as a foundation for policies promoting efficient bookstore operations in HEI and other similar academic settings.